Renal Hemodynamics in AKI: In Search of New Treatment Targets - Matejovic, Martin; Ince, Can; Chawla, Lakhmir S; Blantz, Roland; Molitoris, Bruce A; Rosner, Mitchell H; Okusa, Mark D; Kellum, John A; Ronco, Claudio; ADQI XIII Work Group (Journal of the American Society of Nephrology, 2016)
Novel therapeutic interventions are required to prevent or treat AKI. To expedite progress in this regard, a consensus conference held by the Acute Dialysis Quality Initiative was convened in April of 2014 to develop recommendations for research priorities and future directions. Here, we highlight the concepts related to renal hemodynamics in AKI that are likely to reveal new treatment targets on investigation. Overall, we must better understand the interactions between systemic, total renal, and glomerular hemodynamics, including the role of tubuloglomerular feedback. Furthermore, the net consequences of therapeutic maneuvers aimed at restoring glomerular filtration need to be examined in relation to the nature, magnitude, and duration of the insult. Additionally, microvascular blood flow heterogeneity in AKI is now recognized as a common occurrence; timely interventions to preserve the renal microcirculatory flow may interrupt the downward spiral of injury toward progressive kidney failure and should, therefore, be investigated. Finally, development of techniques that permit an integrative physiologic approach, including direct visualization of renal microvasculature and measurement of oxygen kinetics and mitochondrial function in intact tissue in all nephron segments, may provide new insights into how the kidney responds to various injurious stimuli and allow evaluation of new therapeutic strategies.
Keywords: clinical nephrology; biomedicínský výzkum; hemodynamics and vascular; regulation; Acute Kidney Injury; acute renal failure; Humans; Renal Circulation; Hemodynamics; hemodynamika; renální oběh; lidé; Biomedical Research; akutní poškození ledvin